Effects of Resistance Training Prior to Total Hip or Knee Replacement on Post-operative Recovery in Functional Performance: A Systematic Review and Meta-Analysis - Jørgensen, Stian Langgård; Kierkegaard, Signe; Bohn, Marie Bagger; Aagaard, Per; Mechlenburg, Inger (Frontiers in Sports and Active Living, 2022)
Objective: To evaluate the effectiveness of preoperative resistance training in patients allocated to TJR surgery on selected post-operative outcomes, via a meta-analysis of studies using exercise modalities and loading intensities objectively known to promote gains in muscle size and strength in adults of young-to-old age. Design: A systematic review and meta-analysis. Literature Search: Cochrane Central, MEDLINE, EMBASE, and PEDro were searched on August 4th 2021. Study Selection: Randomized Controlled Trials (RCTs) were included if (i) they compared preoperative lower-limb-exercises before TJR with standard care, (ii) explicitly reported the exercise intensity, and (iii) reported data on functional performance. Data Synthesis: This systematic review and meta-analysis is reported in accordance with the PRISMA reporting guidelines. A random effects model with an adjustment to the confidence interval was performed for pooling the data. Results: One thousand studies were identified. After applying exclusion criteria, five RCTs were located including 256 participants (mean age ranged from 61 to 72 years, 54% women). Moderate-to-large improvements in functional performance and maximal knee extensor strength were observed at three months after surgery along with small-to-moderate effects 12 months post-operatively. For patient-reported outcomes, small-to-moderate improvements were observed at three months post-operatively with no-to-small improvements at 12 months. Conclusion: Prehabilitation efforts involving progressive resistance training provides an effective means to improve postoperative outcomes related to functional performance, knee extensor strength and patient-reported outcome in patients undergoing TJR. Due to large methodological diversity between studies, an optimal loading intensity remains unknown.